Cytotoxic Activity on MCF-7 Cells and in Silico Study of Sapogenin Steroids From Trigonella foenum-graecum L. - Kurnia Agustini; Firdayani Firdayani; Churiyah Churiyah (Indonesian Society for Cancer Chemoprevention, 2015)
Trigonella foenum-graecum (TFG) is one of medicinal plants containing several steroidal sapogenins, such as diosgenin, yamogenin, gitogenin, tigogenin and trigoneoside, and also alkaloid trigonellin and some flavonoids such as vitexin, isovitexin, orientin, isoorientin, which has many activities, such as antidiabetic, estrogenic, and also anticancer. As phytoestrogen, TFG was predicted to have potency as Selective Estrogen Receptor Modulators (SERMs) which is used for hormonal-dependent breast cancer treatment. This experiment was carried out to investigate interaction of some sapogenin steroids and flavonoids in TFG to estrogen receptor alpha (ERα) and its activity to breast cancer cell line as confirmation. In silico prediction was carried out to investigate their estrogenic activity by analyzing their binding affinity to ERα using AutoDock Vina program. In vitro activity confirmation of TFG extract and its fractions were carried out using MTT assay on Erα-positive human breast cancer cell line, MCF-7. Results showed that free binding energies of diosgenin and yamogenin were -6.4 kcal/mol, estradiol was -6.0 kcal/mol, and tamoxifen was -5.1 kcal/mol. While cytotoxicity assay showed that ethyl acetate fraction gave the lowest IC50 of 41.81 ppm, with total steroid content of 20.03 ppm. From these results, we can conclude that diosgenin and yamogenin have greater binding affinity to ERα comparing to estradiol and tamoxifen. In vitro assay confirmation showed that ethyl acetate fraction has cytotoxic effect on MCF-7 cells.Keywords: Trigonella foenum-graecum, sapogenin steroids, MCF-7, estrogen receptor alpha, binding affinity